SCHIZOPHRENIA AND PERSONALITY DISORDER: HOW THE TWO PATHOLOGIES CAN BE CONFUSED - Dalapícola Camatta, Fernanda; Mariani Silva, Camila (Revista Gênero e Interdisciplinaridade, 2022)
The psychiatric reform brought with it new ways of looking at the crazy individual and, mainly, several transformations became possible with the events that have been happening in the reform process. Schizophrenia and emotionally unstable personality disorder are two pathologies that have gone through studies and stigma breaks. But these are not the only points they have in common, which makes it easier to confuse the diagnoses. In this work, I tried to show some of these symptoms and their appearance in the individual from a case study.